Lamar archaeology : Mississippian chiefdoms in the deep South - Williams, J. Mark.; Shapiro, Gary. (Tuscaloosa, Ala. : University of Alabama Press, 1990)
A Dan Josselyn Memorial Publication Lamar Archaeology provides a comprehensive and detailed review of our knowledge of the late prehistoric Indian societies in the Southern Appalachian area and its peripheries. These Lamar societies were chiefdom-level groups who built most of the mounds in this large region and were ancestors of later tribes, including the Creeks and Cherokees. This book begins with a history of the last 50 years of archaeological and historical research and brings together for the first time all the available data on this early culture.
pt. 1. Lamar archaeology -- pt. 2. Time and space -- pt. 3. Case studies.
"A Dan Josselyn memorial publication."
Includes bibliographical references (pages 231-252) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Lamar culture; Indians of North America -- Southern States -- Antiquities; Chiefdoms -- Southern States; Southern States -- Antiquities; Peuples autochtones -- États-Unis (Sud) -- Antiquités.; Chefferie (Anthropologie) -- États-Unis (Sud); États-Unis (Sud) -- Antiquités.; HISTORY -- State & Local -- General; Antiquities; Chiefdoms; Indians of North America -- Antiquities; Lamar culture; Southern States